Ce-NiMo / NF catalyst, preparation method and application of Ce-NiMo / NF catalyst in field of biomass electrooxidation

By preparing the CE-NIMO/NF catalyst, the problem of unable to drive large current density at a lower potential of the nickel catalyst can be solved, and the high-efficiency fibrodytal oxidation and electrocatalytic stability are achieved, which is better than the traditional RUO2 catalyst.

CN119372701AActive Publication Date: 2025-01-28CHONGQING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411493811.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Nickel-based catalysts cannot drive high current density at low overpotentials, and their catalytic performance is poor.

Method used

The CE-NIMO/NF catalyst is used to prepare foam nickel to prepare a catalyst with high-active oxygen adsorption capabilities in combination with water thermal reactions and reduction reactions.

Benefits of technology

Under a lower potential, it can drive a large current density, significantly improved the oxidation activity and electrocatalytic stability, and is better than the RUO2 catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372701A_ABST
    Figure CN119372701A_ABST
Patent Text Reader

Abstract

The invention discloses a Ce-NiMo / NF catalyst, a preparation method and application of the Ce-NiMo / NF catalyst in the field of biomass electrooxidation, and belongs to the technical field of catalyst preparation. The trace rare earth element Ce is doped into the transition metal NiMo, a heterogeneous interface of CeO2 and NiMo is constructed, a more favorable bonding environment is created, the active oxygen adsorption capacity is improved, and therefore the furfural oxidation activity is improved. An anode OER reaction is replaced with an organic electro-oxidation reaction, large-current-density biomass electro-oxidation coupling water electrolysis hydrogen production is driven under the low overpotential, 500 mA cm <-2 > industrial water decomposition current density can be driven under the low voltage of 1.39 V vs RHE, the current density is only reduced by 6% when continuous testing is conducted for 200 h in an electrolytic cell, and the hydrogen production efficiency is greatly improved. And excellent electrocatalytic activity and stability are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a Ce-NiMo / NF catalyst, a preparation method and application thereof in the field of biomass electro-oxidation. Background Art

[0002] The raw materials for hydrogen production by water electrolysis are clean and environmentally friendly, and the electrolysis products are only H2 and O2. However, the reaction rate of the anode oxygen evolution reaction (OER) is slow, resulting in a high oxygen evolution overpotential, which directly reduces the overall energy conversion efficiency and increases the cost of electrolysis. In the production of hydrogen by water electrolysis, the added value of the anode product O2 is low, and the H2 and O2 produced by the two electrodes are easily mixed in the reactor, which poses a safety hazard. Therefore, by using biomass platform compounds such as pentahydroxymethylfurfural (HMF), furfural (FA), glucose and glycerol as raw materials, the biomass electro-oxidation is coupled with water electrolysis to produce hydrogen, which can significantly reduce the overpotential of the reaction and achieve efficient production of hydrogen and high value-added chemicals. The oxidation process of FA is a complex process of electron and proton transfer. With the increase of current density, it will gradually lose the advantages of the furfural electrochemical oxidation reaction (FOR), resulting in a gradual increase in the oxidation potential of FA, and a decrease in the Faraday efficiency (FE) and selectivity. Therefore, it is urgent to develop low-cost, high catalytic activity and high stability catalytic electrode materials.

[0003] Marisa Ketkaew et al. reported a method of preparing Pt / Au Janus particles as bifunctional electrocatalysts by bipolar electrodeposition. The bipolar electrochemical method was used to achieve the simultaneous electrochemical conversion of furfural acid and furfuryl alcohol during the oxidation and reduction of furfural. However, these conversion reactions often rely on precious metal catalysts, such as gold (Au), palladium (Pd) and platinum (Pt). The high price and poor reaction conditions greatly limit the application of precious metal catalysts in industrialization. Therefore, in order to improve the reaction efficiency of the electrocatalytic process, the design and preparation of efficient and stable oxygen evolution electrocatalysts has become the key to the development of electrocatalytic hydrogen production technology. For HER performance, due to the high temperature calcination of the precursor, the performance of the catalyst with too large a surface area will decrease, and there is a problem that it cannot drive a large current density at a low overpotential. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a Ce-NiMo / NF catalyst, a preparation method and its application in the field of biomass electro-oxidation, so as to solve the technical problem that nickel-based catalysts cannot drive large current density at a low overpotential and have poor catalytic performance.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a Ce-NiMo / NF catalyst, comprising the following steps:

[0006] S1. Pre-treat the nickel foam, then dissolve the nickel salt, molybdenum salt, cerium salt and raw material one in water and stir for 15-25 minutes, then place the mixed solution and the pre-treated nickel foam (nickel foam is used as a supporting substrate for the nickel-based catalyst) at 140-160° C. for hydrothermal reaction for 5-7 hours to obtain a precursor Ce-NiMoO4 / NF; the raw material one is ammonium fluoride or urea; the molar ratio of the nickel salt, molybdenum salt, cerium salt and raw material one is 3-5:3-5:0.5-1.5:7-9;

[0007] S2. Place the precursor Ce-NiMoO4 / NF in a reducing atmosphere and perform a reduction reaction at 500-600°C for 1.5-2.5h to obtain a catalyst Ce-NiMo / NF.

[0008] The rare earth element Ce, due to its empty or half-full 4f electron shell structure and low electronegativity, brings the possibility of dynamic adjustment to the electronic configuration of the d-band active center and enhances the spin-orbit coupling effect. The three-dimensional electron cloud configuration of the nickel-based catalyst promotes the effective transfer of electrons, while the unique properties of the eg orbital act as a "bridge" to deepen the interaction between the metal site and the oxygen atom, allowing the furfural molecules to more smoothly undergo the adsorption, conversion and desorption stages during the electrocatalytic oxidation process, thereby optimizing the reaction path and improving efficiency.

[0009] On the basis of the above technical solution, the present invention can also be improved as follows:

[0010] Furthermore, the pretreatment process of the nickel foam is: placing the nickel foam in ethanol and hydrochloric acid respectively, and ultrasonically treating it at 15-25KHz for 15-25min.

[0011] Furthermore, the nickel salt is nickel nitrate or nickel sulfate, the molybdenum salt is sodium molybdate or ammonium molybdate, and the cerium salt is cerium nitrate or cerium sulfate.

[0012] Furthermore, the heating rate during the hydrothermal reaction is 2-3°C / min; and the heating rate during the reduction reaction is 4-5°C / min.

[0013] Furthermore, the temperature of the hydrothermal reaction was 150° C. and the time was 6 h.

[0014] Furthermore, the reduction reaction temperature was 550° C. and the time was 2 h.

[0015] Furthermore, the reducing atmosphere is a mixture of H2 and N2 in a volume ratio of 5-15:85-95.

[0016] The invention also discloses a Ce-NiMo / NF catalyst prepared by the preparation method.

[0017] The invention also discloses the application of Ce-NiMo / NF catalyst in the field of biomass electro-oxidation.

[0018] The beneficial effects of the present invention are:

[0019] 1. The present invention constructs a heterogeneous interface between CeO2 and NiMo by doping a trace amount of rare earth element Ce into transition metal NiMo, creates a more favorable bonding environment, improves the active oxygen adsorption capacity, and thus enhances the furfural oxidation activity. In addition, the organic electro-oxidation reaction is used instead of the anode OER reaction to achieve high current density biomass electro-oxidation coupled with water electrolysis to produce hydrogen at a lower overpotential, showing excellent electrocatalytic activity and stability.

[0020] 2. When the Ce-NiMo / NF catalyst prepared by the present invention is used for furfural electrooxidation coupled with water electrolysis to produce hydrogen, it is sufficient to drive 500 mA cm at a low voltage of 1.39 V vs RHE. -2 The catalytic activity is significantly better than that of RuO2 (500 mA cm at 1.63 V vs RHE). -2 Meanwhile, the corresponding furoic acid (FAC) selectivity and Faraday efficiency (FE) reached 99.43% and 97.68%, respectively.

[0021] 3. The electrolytic cell using the Ce-NiMo / NF prepared by the present invention as the anode electrode only needs a battery voltage of 1.9V to drive 580mA cm under industrial conditions. -2 The current density of the catalyst was only reduced by 6% after continuous testing in the electrolyzer for 200 hours, showing excellent electrochemical stability. The Ce-NiMo / NF catalyst was used in the oxidation of biomass such as HMF, glucose and glycerol, and showed good electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a preparation flow chart of the present invention;

[0023] Figure 2 SEM images of Ce-NiMo / NF with different Ce concentrations, wherein (a) is the SEM image of Ce-NiMo / NF with a Ce concentration of 5 mM, (b) is the SEM image of Ce-NiMo / NF with a Ce concentration of 10 mM, (c) is the SEM image of Ce-NiMo / NF with a Ce concentration of 15 mM, and (d) is the SEM image of Ce-NiMo / NF with a Ce concentration of 20 mM;

[0024] Figure 3 is the XRD pattern of Ce-NiMoO4 / NF;

[0025] Figure 4XRD patterns of Ni, NiMo / NF and Ce-NiMo / NF;

[0026] Figure 5 The XRD partial magnified images of Ni, NiMo / NF and Ce-NiMo / NF;

[0027] Figure 6 This is the full XPS spectrum of Ce-NiMo / NF;

[0028] Figure 7 XPS spectra of Ni 2p in NiMo / NP and Ce-NiMo / Ni / NF;

[0029] Figure 8 is the XPS spectrum of Ce 3d in Ce-NiMo / NF;

[0030] Fig. 9 XPS spectra of Co 2p in NiMo / NF and Ce-NiMo / NF;

[0031] Fig.10 XPS spectra of O1s in NiMo / NF and Ce-NiMo / NF;

[0032] Fig.11 EPR test results of Ce-NiMo / NF;

[0033] Fig.12 SEM image of Ce-NiMo / NF;

[0034] Fig.13 TEM images of Ce-NiMo / NF at different resolutions;

[0035] Fig.14 HRTEM image of Ce-NiMo / NF;

[0036] Fig.15 SAED image of Ce-NiMo / NF;

[0037] Fig.16 AC-HADDF-STEM image;

[0038] Fig.17 SAED pattern of Ni atomic distance;

[0039] Fig.18 SAED pattern of Mo atomic distance;

[0040] Fig.19 SAED pattern of the longitudinal distance of Ce atoms;

[0041] Fig. 20 SAED pattern of the lateral distance of Ce atoms;

[0042] Fig.21 STEM image of Ce-NiMo / NF nanorods;

[0043] Fig. 22 Activity comparison of Ce-NiMo / NF at different reduction temperatures;

[0044] Fig.23 XRD patterns of Ce-NiMo / NF at different reduction temperatures;

[0045] Fig.24 SEM images of Ce-NiMo / NF at different reduction temperatures, wherein (a) is the SEM image of Ce-NiMo / NF at 450°C, (b) is the SEM image of Ce-NiMo / NF at 500°C, (c) is the SEM image of Ce-NiMo / NF at 550°C, and (d) is the SEM image of Ce-NiMo / NF at 600°C;

[0046] Fig.25 is the XRD pattern of Ce-NiMo / NF at 600℃ reduction temperature;

[0047] Fig.26 Comparison of LSV for electrolysis of water and electrochemical oxidation of furfural;

[0048] Fig. 27 This is a comparison chart of LSV of different materials;

[0049] Fig.28 FOR and OER polarization curves of Ce-NiMo / NF and RuO2 / NF;

[0050] Fig.29 is the Tafel slope plot;

[0051] Fig.30 are the EIS curves of different nickel-based materials in FA solution;

[0052] Fig.31 Cyclic voltammograms of different nickel-based materials at different scan rates;

[0053] Fig.32 is the variation of FA, FAC and FAL concentrations with charge consumption;

[0054] Fig.33 Figure 2 is the FAC selectivity and Faraday efficiency (FE) diagram of Ce-NiMo / NF material;

[0055] Fig.34 The selectivity and FE changes of Ce-NiMo / NF after 6 cycles;

[0056] Fig.35 This is a comparison chart of furoic acid consumption after 6 cycles;

[0057] Fig.36 is the SEM image of Ce-NiMo / NF after 6 cycles;

[0058] Fig.37 Schematic diagram of the flow cell device;

[0059] Fig.38 is the LSV curve of furfural electrolysis;

[0060] Fig.39 The long-term stability of Ce-NiMo / NF;

[0061] Fig.40 LSV curves of Ce-NiMo / NF on different substrates. DETAILED DESCRIPTION

[0062] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0063] Example 1

[0064] A method for preparing a Ce-NiMo / NF catalyst, such as Figure 1 As shown, the following steps are included:

[0065] S1. Place nickel foam in ethanol and hydrochloric acid, respectively, and perform ultrasonic treatment at 15KHz for 25min. Then, dissolve nickel nitrate Ni(NO3)2·6H2O (0.407g, 40mM), sodium molybdate Na2MoO4·2H2O (0.339g, 40mM), cerium nitrate Ce((NO3)3·6H2O) (0.152g, 10mM) and ammonium fluoride NH4F (0.1036g, 80mM) in 35mL water and stir for 15min. Then, mix the mixed solution with 1×1cm 2 The pretreated nickel foam was mixed, heated from room temperature to 140°C at a heating rate of 2°C / min, and subjected to hydrothermal reaction for 7h to obtain the precursor Ce-NiMoO4 / NF;

[0066] S2. Place the precursor Ce-NiMoO4 / NF in a reducing atmosphere (H2:N2=5:95, v:v), then heat the temperature from room temperature to 500°C at a heating rate of 4°C / min, and perform a reduction reaction for 2.5h to obtain the catalyst Ce-NiMo / NF.

[0067] Example 2

[0068] A method for preparing a Ce-NiMo / NF catalyst, such as Figure 1 As shown, the following steps are included:

[0069] S1. Place nickel foam in ethanol and hydrochloric acid, respectively, and perform ultrasonic treatment at 25KHz for 15min. Then, dissolve nickel sulfate (0.407g, 40mM), ammonium molybdate (0.339g, 40mM), cerium nitrate Ce((NO3)3·6H2O) (0.152g, 10mM) and ammonium fluoride NH4F (0.1036g, 80mM) in 35mL water and stir for 25min. Then, mix the mixed solution with 1×1cm 2 The pretreated nickel foam was mixed, heated from room temperature to 160°C at a heating rate of 3°C / min, and subjected to hydrothermal reaction for 5h to obtain the precursor Ce-NiMoO4 / NF;

[0070] S2. The precursor Ce-NiMoO4 / NF was placed in a reducing atmosphere (H2:N2=15:85, v:v), then heated from room temperature to 600°C at a heating rate of 5°C / min, and subjected to a reduction reaction for 1.5h to obtain the catalyst Ce-NiMo / NF.

[0071] Example 3

[0072] A method for preparing a Ce-NiMo / NF catalyst, such as Figure 1 As shown, the following steps are included:

[0073] S1. Place nickel foam in ethanol and hydrochloric acid, respectively, and ultrasonically treat for 20 min at 20 KHz; then dissolve nickel nitrate Ni(NO3)2·6H2O (0.407 g, 40 mM), sodium molybdate Na2MoO4·2H2O (0.339 g, 40 mM), cerium nitrate Ce((NO3)3·6H2O) (0.152 g, 10 mM) and ammonium fluoride NH4F (0.1036 g, 80 mM) in 35 mL of water and stir for 20 min. Then, mix the mixed solution with 1×1 cm 2 The pretreated nickel foam was mixed, heated from room temperature to 150°C at a heating rate of 2°C / min, and subjected to hydrothermal reaction for 6h to obtain the precursor Ce-NiMoO4 / NF;

[0074] S2. The precursor Ce-NiMoO4 / NF was placed in a reducing atmosphere (H2:N2=10:90, v:v), and then heated from room temperature to 550°C at a heating rate of 4°C / min, and subjected to reduction reaction for 2h to obtain the catalyst Ce-NiMo / NF, named Ce 10 .

[0075] Example 4

[0076] The difference between this embodiment and embodiment 3 is that the addition amount of cerium nitrate is adjusted to 5 mM, and the other implementation conditions are the same as those of embodiment 3, and a catalyst Ce-NiMo / NF is obtained, which is named Ce5.

[0077] Example 5

[0078] The difference between this embodiment and embodiment 3 is that the amount of cerium nitrate added is adjusted to 15 mM, and the other implementation conditions are the same as those of embodiment 3 to obtain a catalyst Ce-NiMo / NF, named Ce 15 .

[0079] Comparative Example

[0080] The difference between this comparative example and Example 3 is that the cerium salt is omitted, and the remaining components and preparation process are the same as those in Example 3 to obtain a NiMo / NF catalyst named Ce0.

[0081] The Ce-NiMo / NF material used in the following experiments is the Ce-NiMo / NF catalyst prepared in Example 3.

[0082] Experimental Example 1 Material Characterization

[0083] 1. Microstructure of Ce-NiMo / NF

[0084] Different Ce contents (Ce0, Ce5, Ce 10 and Ce 15 The morphology of Ce-NiMo / NF is as follows: Figure 2 Compared with the densely packed nanorods in the undoped Ce NiMo / NF catalyst (Ce0), the Ce5 and Ce 10 and Ce 15 The spatial structure of the clusters shows that reasonable Ce doping promotes the growth of clusters and exposes more active sites.

[0085] 2. X-ray diffraction analysis

[0086] In order to further confirm the crystal structure, the composition of Ce-NiMo / NF material was analyzed, and the X-ray diffraction (XRD) diagram is shown in the figure Figure 3The diffraction peaks at 2θ–44.5°, 51.8° and 76.4° correspond to the (111), (200) and (220) crystal planes of Ni, and the diffraction peaks at 37.2°, 43.2° and 62.9° correspond to the (111), (200) and (110) crystal planes of NiO, respectively (PDF#44-1159). It can be seen that after hydrogen reduction, NiMoO4 and a part of NiO species are reduced to Ni( Figure 4 ). Due to the low Ce content, no Ce characteristic peak is shown in the XRD spectrum. It is found that the intensity of Ni's characteristic diffraction peak is significantly weakened. The local magnification of the Ni (111) crystal plane area ( Figure 5 ), showing that the (111) crystal plane of Ni shifted by 0.37° at a low angle after Ce doping. This is due to the 3+ The ionic radius is larger than that of Ni 2+ , which causes the Ni lattice to be distorted, which is conducive to the generation of more defects. It is preliminarily confirmed that Ce has been successfully doped into the NiMo material.

[0087] 3. X-ray photoelectron spectroscopy analysis

[0088] The chemical environment and electronic structure of the Ce-NiMo / NF catalyst prepared in Example 3 were investigated by X-ray photoelectron spectroscopy (XPS). Figure 6 As shown in Figure 2, the XPS spectrum of Ce-NiMo / NF shows the presence of Ce, Ni, Mo and O elements. Figure 7 As shown, the peaks at 881.79 and 901.61 eV belong to Ce 3+ , while the peaks at 879.12, 886.03, 892.94, 896.04, 899.19, and 905.04 eV belong to Ce 4+ .like Figure 8 As shown in the Mo 3d spectrum of NiMo / NF catalyst, the peaks at 223.02eV and 232.21eV are similar to those at Mo 3+ The peaks at 229.48 eV and 232.94 eV are related to Mo 4+ After Ce doping, the peaks at 229.13eV and 232.32eV in Ce-NiMo / NF are related to Mo. 3+ The peaks at 229.55eV and 233.01eV are related to Mo 4+ There is an obvious shift of 0.11 eV compared with NiMo / NF, indicating that the charge is transferred from NiMo / NF to Ce and that the Mo oxide undergoes a certain degree of reduction during annealing in H2 atmosphere.

[0089] like Fig. 9As shown in the Ni 2p spectrum of NiMo / NF catalyst, the peaks at 852.91eV and 871.32eV are related to NiO, and the peaks at 855.95eV and 873.70eV are related to Ni 2+ 2p 3 / 2 The peaks at 859.22eV and 877.63eV are related to Ni 2+ 2p 1 / 2 After Ce doping, the peaks at 852.95eV and 871.36eV ​​in Ce-NiMo / NF are related to NiO, and the peaks at 856.05eV and 873.80eV are related to NiO. 2+ 2p 3 / 2 The peaks at 858.83eV and 877.24eV are related to Ni 2+ 2p 1 / 2 The peaks at 862.27eV and 880.68eV are satellite peaks, and the peaks move toward higher binding energies, indicating that electronic interactions cause charge transfer. Fig.10 As shown in the graph, the proportion of oxygen vacancies (Ov) in Ce-NiMo / NF is larger than that in NiMo / NF.

[0090] Ce-NiMo / NF was tested by EPR ( Fig.11 ), the results show that Ce-NiMo / NF has a large number of defect sites. Combined with the XPS analysis results, it shows that the introduction of Ce produces more oxygen vacancies on the catalyst surface, which helps to accelerate the oxidation reaction.

[0091] 4. Scanning electron microscopy and transmission electron microscopy analysis

[0092] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to investigate the micro-nanostructure of Ce-NiMo / NF. Fig.12 and Fig.13 As shown, the integrity of the NiMo nanorod structure and morphology is still maintained after Ce doping. Fig.14 and Fig.15 A high-resolution TEM image of Ce-NiMo / NF is shown. The lattice fringes with interplanar spacing of 0.206 nm and 0.209 nm point to Ni(111), NiO(200), and CeO2(200), respectively, indicating the existence of a heterogeneous interface between NiMo and CeO2. In order to clearly confirm the existence of a heterogeneous interface between NiMo and CeO2, an aberration-corrected (AC) high-angle annular dark-field scanning TEM (HAADF-STEM) measurement was performed ( Fig.16). The heterogeneous interface can be clearly found based on the arrangement of atoms. The close interface interaction between CeO2 and NiMo helps to cause local electronic configuration and internal electronic rearrangement, improve the active oxygen adsorption capacity, and thus enhance the oxidation activity of the catalyst. Fig.17 and Fig.18 As shown, the distances between Ni atoms and Mo atoms are (lateral distance) and (longitudinal distance), compared with the Cif of Ni crystal, the atomic distance increases due to the larger atomic radius of Mo. Fig.19 and Fig. 20 As shown in the figure, the measured lateral and vertical spacings between Ce atoms are and It is consistent with its cubic structure and is consistent with the Cif parameters of CeO2 crystal. EDX element mapping ( Fig.21 ) also demonstrated the uniform distribution of Ni, Mo and Ce on the nanorods.

[0093] Experimental Example 2 Effect of reduction temperature on the activity of Ce-NiMo / NF catalyst

[0094] Comparison of the catalytic activity and composition of Ce-NiMo / NF catalysts at different reduction temperatures shows that the catalytic activity is best when the reduction temperature is 550℃ ( Fig. 22 ). The crystal compositions at reduction temperatures of 450°C, 500°C, and 550°C are the same. As the reduction temperature increases, the crystallinity becomes better and better ( Fig.23 ), the nanorods grow more densely ( Fig.24 When the reduction temperature was raised to 600°C, SEM revealed that the catalyst surface morphology changed and new phases were generated, resulting in a weakening of the catalytic activity ( Fig.25 ).

[0095] Experimental Example 3 Electrocatalytic Activity

[0096] 1. Linear sweep voltammetry (LSV) test

[0097] The electrocatalytic activity of furfural electrochemical oxidation reaction (FOR) and anodic oxygen evolution reaction (OER) was studied in a three-electrode H-type electrolyzer. The anolyte of the experimental group was 1M potassium hydroxide solution containing 0.1M furfural, and the anolyte of the control group was 1M potassium hydroxide solution without furfural. The catholyte of both groups was 1M potassium hydroxide, the reaction solution volume was 30mL, and the reaction temperature was 25°C. The specific steps are as follows: the electrochemical activity was tested using an electrochemical station (CHI1140C) in an H-type electrolyzer with a three-electrode system, the reference electrode was Hg / HgO (1M KOH), the counter electrode was a graphite sheet (2cm×2cm×2mm), the hydrothermally synthesized sample was used as the working electrode, and all electrochemical tests were carried out at room temperature (25°C). Before the linear sweep voltammetry (LSV) test, the activated electrode was charged at 50mV s -1 40 voltammetry (CV) cycles were performed at a scan rate of 5 mV s -1 LSV was performed at a scan rate of 100 Å using 30 mL of 1 M KOH solution and 0.1 M FA as the anode electrolyte and 30 mL of 1 M KOH solution as the cathode electrolyte, separated by an anion exchange membrane.

[0098] The results are as follows Fig.26 As shown, when the anolyte is only 1 M KOH (control group), there is a small oxidation peak at 1.38 V vs. RHE caused by Ni 2+ Oxidized to Ni 3+ , resulting in the need for 500mAcm -2 When the anolyte is 1 M KOH and 0.1 M furfural (experimental group), at 500 mA cm -2 At a current density of 1.39 V vs. RHE, only a voltage of 1.39 V vs. RHE is required to drive the furfural electrochemical oxidation reaction (FOR).

[0099] like Fig. 27 As shown in Figure 2, Ce doping has better furfural electrochemical oxidation activity, reaching 500 mA cm compared with NiMo / NF catalyst. -2 The current density voltage is reduced by 90mV, which is 500mAcm compared with RuO2 catalyst. -2 The current density voltage decreased by 270mV ( Fig.28 ), RuO2 catalyst can only reach 500mA cm at 1.63Vvs RHE -2 When Ce-Ni / NF catalyst was synthesized without adding Mo source, a large oxidation peak was observed at 1.45V vs. RHE. 2+ Oxidized to Ni 3+, resulting in a sharp drop in its electrochemical activity. However, the precursor Ce-NiMoO4 / NF has comparable electrochemical activity to the nickel foam substrate.

[0100] 2. Tafel slope analysis

[0101] In order to determine the effect of Ce doping on the reaction kinetics, Tafel slope analysis was performed based on the LSV curve. The results are shown in Fig.29 As shown in Figure 2, the Tafel slope of Ce-NiMo / NF is 25.43 mV dec. -1 , lower than NiMo / NF (29.42mV dec -1 )、Ce-Ni / NF(32.32mV dec -1 )、precursor Ce-NiMoO4 / NF(38.3mV dec -1 ) and substrate NF (40.08mV dec -1 ), indicating that Ce-NiMo / NF catalyst has the highest FOR activity and the fastest reaction kinetics.

[0102] 3. Electrochemical impedance spectroscopy test

[0103] In order to further explore the catalytic activity of the catalyst, the electrochemical impedance spectroscopy (EIS) test was performed on the Ce-NiMo / NF material. Fig.30 As shown in Figure 2, Ce-NiMo / NF exhibits the smallest Rct value, indicating that the charge transfer between the electrode and the electrolyte is faster. Then, cyclic voltammograms (CV) at different scan rates were performed in the non-Faraday region. Fig.31 As shown in Figure 2, Ce-NiMo / NF has the largest double-layer capacitance (4.34 mF cm -2 ) and the largest electrochemically active surface area (108.5 cm 2 ), which indicates that Ce-NiMo / NF has more active sites.

[0104] 4. Analysis of electrolysis products

[0105] After electrolysis, the reaction products and products were quantitatively and qualitatively analyzed by high performance liquid chromatography. The specific steps were as follows: at 35°C, a UV-visible detector (220 nm) and a C18 column (4.6 mm × 150 mm × 5 μm, gasket set GWS) were used, and the reaction mixture was concentrated at 0.6 mL min-1. -1The product formation and reactant consumption during the constant potential electrolysis were quantitatively and qualitatively analyzed at a flow rate of 1.3 V. The HPLC mobile phase consisted of a mixture of 50% water and 50% acetonitrile. The instrument was calibrated using a standard curve generated using commercially available products for the quantitative determination of FA, FAC, and FAL. Electrochemical tests were performed at an anode potential of 1.3 V vs. RHE.

[0106] The results are as follows Fig.32 As shown in the figure, as the electrolysis power increases from 0C to 400C, the concentrations of furfural (FA) and furoic acid (FAC) change linearly to produce trace amounts of FAL, which may be produced by the disproportionation reaction of FA in a strong alkaline solution. The carbon balance during the reaction is always close to 100%, indicating that the polymerization of furfural can be ignored.

[0107] Experimental Example 4 Stability of Ce-NiMo / NF Catalyst

[0108] By investigating the effects of different electrolysis potentials on the FAC selectivity and Faradaic efficiency (FE) of Ce-NiMo / NF electrode, Fig.33 As shown in the figure, with the increase of electrolysis potential, the Faradaic efficiency of FAC gradually decreases, while the selectivity of FAC remains almost unchanged. This is because the competitiveness of OER becomes stronger and stronger with the increase of potential, consuming a considerable part of the electrolysis electricity.

[0109] The stability of Ce-NiMo / NF catalyst is as follows Fig.34 and Fig.35 As shown in the figure, by continuous electrolysis at an anode potential of 1.39 V vs. RHE for 6 cycles, each cycle consumes 300C of electricity, and the selectivity of FAC decreases from 99.43% to 95.01%, and the Faraday efficiency decreases from 97.68% to 92.39%. In addition, after 6 complete electrolysis cycles, the selectivity and Faraday efficiency of FAC only show a slight decrease, and the LSV curve does not change much. As shown in the SEM image ( Fig.36 ), the nanorod structure as well as the nanoparticles and nanoneedle-like structures on the nanorods still exist. Overall, this indicates that Ce-NiMo / NF has good FOR stability.

[0110] Experimental Example 5 Battery Experiment

[0111] 1. By constructing a flow electrolyzer (Ce-NiMo / NF(+)||NiPt4 / NM(-)), the industrial anode furfural electro-oxidation coupled with cathode hydrogen evolution reaction is simulated. The schematic diagram of the device is shown in the figure. Fig.37 As shown, the anolyte of the experimental group was 1M potassium hydroxide solution containing 0.1M furfural, the anolyte of the control group was 1M potassium hydroxide solution without furfural, the catholyte of both groups was 1M potassium hydroxide, the reaction temperature was 50°C, and the anion exchange membrane used was porous membrane ZP-1239.

[0112] The results are as follows Fig.38 As shown, up to 500mA cm -2 The cell voltage required for water electrolysis is 2.06 V, while furfural electrolysis only requires 1.78 V; furfural electrolysis only requires a cell voltage of 1.9 V to achieve a current density of 580 mA cm -2 The current density shows that the efficiency of furfural electrooxidation coupled with water electrolysis to produce hydrogen is better, and it has obvious thermodynamic and kinetic advantages over water electrolysis. Fig.39 As shown, after continuous testing in the electrolyzer for 200 h, the current density only decreased by 6%, indicating that the Ce-NiMo / NF catalyst has excellent electrochemical stability.

[0113] 2. The electrochemical activity was tested using an electrochemical station (CHI 1140C) in an H-type electrolytic cell with a three-electrode system. The reference electrode was Hg / HgO (1M KOH), the counter electrode was a graphite sheet (2 cm × 2 cm × 2 mm), and the hydrothermal synthesized sample was used as the working electrode. All electrochemical tests were performed at room temperature (25 °C). Before the linear sweep voltammetry (LSV) test, the activated electrode was charged at 50 mV s -1 40 voltammetry (CV) cycles were performed at a scan rate of 5 mV s -1 LSV was performed at a scan rate of , using 30 mL of 1 M KOH solution with 0.1 M HMF, glucose and glycerol as the anode electrolyte, and 30 mL of 1 M KOH solution as the cathode electrolyte, separated by an anion exchange membrane.

[0114] The results are as follows Fig.40 As shown in the figure, the Ce-NiMo / NF catalyst exhibits good electrocatalytic activity in the oxidation of biomass such as HMF, glucose and glycerol.

Claims

1. A method for preparing a Ce-NiMo / NF catalyst, characterized in that: The following steps are involved: S1. Pre-treat the nickel foam, then dissolve the nickel salt, molybdenum salt, cerium salt and raw material one in water and stir for 15-25 minutes, then place the mixed solution and the pre-treated nickel foam at 140-160° C. for hydrothermal reaction for 5-7 hours to obtain a precursor Ce-NiMoO4 / NF; the raw material one is ammonium fluoride or urea; the molar ratio of the nickel salt, molybdenum salt, cerium salt and raw material one is 3-5:3-5:0.5-1.5:7-9; S2. Place the precursor Ce-NiMoO4 / NF in a reducing atmosphere and perform a reduction reaction at 500-600°C for 1.5-2.5h to obtain a catalyst Ce-NiMo / NF.

2. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The pretreatment process of the nickel foam is as follows: placing the nickel foam in ethanol and hydrochloric acid respectively, and ultrasonically treating the nickel foam at 15-25 KHz for 15-25 minutes.

3. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The nickel salt is nickel nitrate or nickel sulfate, the molybdenum salt is sodium molybdate or ammonium molybdate, and the cerium salt is cerium nitrate or cerium sulfate.

4. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The heating rate during the hydrothermal reaction is 2-3°C / min; the heating rate during the reduction reaction is 4-5°C / min.

5. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150° C. and the time is 6 hours.

6. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The reduction reaction was carried out at a temperature of 550° C. and for a period of 2 h.

7. The method for preparing the Ce-NiMo / NF catalyst according to claim 1, characterized in that: The reducing atmosphere is a mixture of H2 and N2 in a volume ratio of 5-15:85-95.

8. A Ce-NiMo / NF catalyst, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Ce-NiMo / NF catalyst according to claim 8 in the field of biomass electro-oxidation.

Citation Information

Patent Citations

  • Hydrotreating catalyst and preparation method thereof

    CN111318286A

  • Ruthenium-modified molybdenum-nickel nanorod composite catalyst as well as preparation method and application thereof

    CN114875442A

  • Nickel-iron-cerium catalytic material, preparation method thereof and application of nickel-iron-cerium catalytic material in electrolyzed water

    CN117248219A